Ketimpangan Pembangunan Daerah di Era Otonomi Daerah - Habibi, Muhammad (Multiverse: Open Multidisciplinary Journal, 2024)
The persistent development inequality in Indonesia, characterized by its archipelagic nature with approximately 17,000 islands, is a critical issue. The vast territory poses significant challenges, particularly for the outermost or remote areas that often lag in development. This research addresses the factors inhibiting regional development despite the implementation of regional autonomy. Using qualitative methods, data was collected through interviews and document analysis to identify these factors. The findings reveal that lack of road access, absence of natural resources, and inadequate human resource capacity are major impediments. Additionally, bureaucratic inefficiencies and insufficient government policies further exacerbate the problem. The study argues that the central government must provide continuous support in developing regional infrastructure and human resources. Enhancing these aspects can stimulate economic growth, foster regional independence, and reduce development disparities across the nation. Thus, a collaborative effort between central and local governments is crucial for achieving balanced national development.